Entrepreneurial Finance Strategies for Startup Success - Ermawati, Yana (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
This study explores entrepreneurial finance strategies crucial for startup success. The purpose is to analyze venture capital dynamics, bootstrapping, crowdfunding mechanisms, and financial planning. Research design involves a literature review synthesizing findings from scholarly articles. Findings indicate that VC funding offers capital and expertise but is competitive, while bootstrapping provides autonomy and encourages resourcefulness. Crowdfunding offers alternative financing but requires effective marketing and community engagement. Financial planning fosters sustainable growth through prudent resource management. Discussion underscores the significance of understanding financing options and their implications. Entrepreneurs must weigh trade-offs, investors acknowledge diverse financing mechanisms, and policymakers foster supportive environments. Implications extend to economic growth and innovation. By adopting suitable financing strategies, startups enhance their chances of success, contributing to vibrant entrepreneurial ecosystems.